2014
DOI: 10.3390/cancers6042012
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Specific for STAT3β Reveal Its Contribution to Constitutive STAT3 Phosphorylation in Breast Cancer

Abstract: Since its discovery in mice and humans 19 years ago, the contribution of alternatively spliced Stat3, Stat3β, to the overall functions of Stat3 has been controversial. Tyrosine-phosphorylated (p) Stat3β homodimers are more stable, bind DNA more avidly, are less susceptible to dephosphorylation, and exhibit distinct intracellular dynamics, most notably markedly prolonged nuclear retention, compared to pStat3α homodimers. Overexpression of one or the other isoform in cell lines demonstrated that Stat3β acted as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…More recent studies demonstrated that increased co-expression of STAT3β relative to STAT3α was shown to increase levels of pSTAT3 and to prolong its phosphorylation (17), presumably through resistance to dephosphorylation of STAT3β homodimers and STAT3α/β heterodimers (17). We developed monoclonal antibodies that recognize the 7 C-terminal amino acids unique to STAT3β (CT7) and were specific for STAT3β (13). Using our STAT3β-specific antibodies, we found that STAT3β protein levels, similar to STAT3α proteins levels, were elevated in 7 of 8 NSCLC cell lines each by 2–6 fold compared to HBEC-3KT (Figure 1B and 1D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies demonstrated that increased co-expression of STAT3β relative to STAT3α was shown to increase levels of pSTAT3 and to prolong its phosphorylation (17), presumably through resistance to dephosphorylation of STAT3β homodimers and STAT3α/β heterodimers (17). We developed monoclonal antibodies that recognize the 7 C-terminal amino acids unique to STAT3β (CT7) and were specific for STAT3β (13). Using our STAT3β-specific antibodies, we found that STAT3β protein levels, similar to STAT3α proteins levels, were elevated in 7 of 8 NSCLC cell lines each by 2–6 fold compared to HBEC-3KT (Figure 1B and 1D).…”
Section: Resultsmentioning
confidence: 99%
“…The blots incubated with primary antibody overnight at 4°C. The primary STAT3β mouse monoclonal antibody was generated in our laboratory against the C-terminal 7 amino acid residues unique to STAT3β (13) and used at a dilution of 1:1000. The membranes were incubated with horseradish-peroxidase (HRP)-conjugated secondary goat anti-mouse antibody (Santa Cruz, catalog# sc2005) at 1:5,000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the antibody specific for STAT3α, we used the monoclonal antibody recently developed to detect STAT3β. 27 The result demonstrated that for the most part the expected protein levels were elevated after co-expression of these variants when compared with the EV ( Figure 4a , left panel). However, expression of only the STAT3β variants was associated with a concomitant increase in STAT3Sα.…”
Section: Resultsmentioning
confidence: 88%
“…After blocking with non-fat milk, the membrane was probed with primary antibodies against proteins of interest. The primary antibodies included anti-STAT3pan (124H6, from Cell Signaling Technology, Danvers, MA, USA), anti-STAT3α (9D8, ab119352, from Abcam, Cambridge, MA, USA), anti-STAT3β, 27 anti-phospho-STAT3 (Tyr-705) (D3A7) (#9145, from Cell Signaling Technology), anti-NFKBIA (L35A5, from Cell Signaling Technology), anti-NFKBIZ (TA502768S, from OriGene Technologies, Rockville, MD, USA), anti-α-tubulin (sc-8035, from Santa Cruz Biotechnology, Dallas, TX, USA), anti-β-actin (#4967, from Cell Signaling Technology) and anti-histone-H3 (Abcam, #ab1791). After blotting with the HRP-conjugated secondary antibody, the membrane was developed using a chemiluminescence HRP substrate kit (Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%